Tackling Youth Exclusion in the UK: Challenges for Current Policy and Practice - Eldin Fahmy (Social Work and Society)
Addressing the situation of marginalised youth has been central to policy initiatives directed at tackling poverty and social exclusion in the UK in recent years. The period since 1997 has therefore witnessed a renewed emphasis upon the development of a coherent framework for youth policy in the UK with the goal of promoting youth inclusion and participation. Nevertheless, understanding the nature and prospects for policies designed to tackle youth exclusion involves a deeper interrogation of the concept of 'social exclusion' and its applications within UK policy debates. Here, it is argued that whilst considerable progress has been made in the promotion of a coherent and integrated strategy for youth inclusion in the UK such policies are unlikely to be effective without a re-conceptualisation of the nature of social exclusion, its causes and consequences. In particular, a more holistic understanding is called for which extends beyond an emphasis on labour market activation policies as a response to the circumstances facing marginalised youth in the UK and elsewhere, and one which interrogates exclusionary processes and institutional practices rather than addressing only the symptoms of disadvantage.